Anti-Gad 65 encephalitis with rapidly progressive temporal atrophy reveals the involvement of the temporal lobe in the neuroanatomical basis of palilalia. (March 2023) - Zilioli, Alessandro; Misirocchi, Francesco; Pancaldi, Beatrice; Mannini, Elisa; Mutti, Carlotta; Zinno, Lucia; Florindo, Irene; Spallazzi, Marco; Parrino, Liborio
Abstract: Palilalia is an acquired speech disorder characterized by the reiteration of words or sentences, historically divided in two main subtypes: "palilalie heterolalique" and "palilalie homolalique". In the former, the reiteration is characterized by rate increase and volume decrease, while in the latter these features remain unaltered. While the "heterolalique" subtype has been mainly observed in the context of basal ganglia diseases, the neuroanatomical basis of the "homolalique" subtype has never been completely clarified. Here we report the case of an 81 years-old woman who developed an extremely repetitive and perseverative language with "homolalique" subtype features and a rapidly progressive course with severe bitemporal atrophy, as a consequence of anti-glutamic acid decarboxylase 65 (GAD 65) antibodies encephalitis. To the best of our knowledge, this is the first report of palilalia in the context of anti-GAD 65 encephalitis. Through the support of voxel-based morphometry and hippocampal subfields analysis, this case study provides a fascinating way of understanding the networks responsible for palilalia, shedding some light on the critical role of temporal areas in the onset of this rare language disorder.